Analysis of coagulation alteration and its correlation with β2-microglobulin in 371 patients with newly diagnosed multiple myeloma - Miao Hu; Yanfen Ma; Keli Jia; SaSa Liu; Huarong Jing; Ruicheng Li (Hematology)
Objectives To explore the changes in the coagulation function of patients newly diagnosed with multiple myeloma (MM) at different stages and with different M protein types, and to analyze the correlation between coagulation indexes and β2-microglobulin (β2-MG).Methods A total of 371 Patients with newly diagnosed MM (n = 371) and healthy controls (n = 48) were selected from January 2016 to December 2022. Baseline data, β2-MG and coagulation index values were collected. Indexes included prothrombin time (PT), activated partial thromboplastin time (APPT), fibrinogen (FIB), thrombin time (TT), fibrinogen degradation products (FDP), and D-dimer(D-D). Patients were divided into different groups according to the Durie-Salmon staging system (DS), the International Staging System (ISS) and disease classification (M protein type). The levels of these six indexes were compared among the groups and the correlation between each index and β2-MG was analyzed.Results Compared to the normal control group, the levels of PT, FIB, TT, FDP and D-D in the MM group were significantly higher (all P < 0.001). As DS and ISS staging increased, the levels of PT, TT, FDP and D-D also increased significantly (all P < 0.001). β2-MG was positively correlated with PT, TT, and FDP levels (Spearman r = 0.157, 0.270, 0.108, respectively; all P < 0.05), and negatively correlated with FIB (r = −0.220, P < 0.001). Significant differences existed in the levels of these six indexes among different M protein types (all P < 0.001). Among them, PT and APTT increased significantly in the IgA-κ group, FIB increased in the λ light chain group, TT increased in the IgG-κ group, FDP increased in the κ light chain group, and D-D increased in the IgG-λ group.Conclusions The degree of coagulation dysfunction in MM patients increases with disease stage and abnormal increases of various coagulation indicators occur in different M protein types and are closely related to β2-MG.